2019
DOI: 10.1111/1365-2435.13317
|View full text |Cite
|
Sign up to set email alerts
|

Biological invasion: The influence of the hidden side of the (epi)genome

Abstract: Understanding the mechanisms underlying biological invasions and rapid adaptation to global change remains a fundamental challenge, particularly in small populations lacking in genetic variation. Two understudied mechanisms that could facilitate adaptive evolution and adaptive plasticity are the increased genetic variation due to transposable elements (TEs), and associated or independent modification of gene expression through epigenetic changes. Here, we focus on the potential role of these genetic and non‐ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
66
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 157 publications
(224 reference statements)
0
66
0
4
Order By: Relevance
“…Epigenetic mechanisms have also been suggested to be relevant in facilitating phenotypic changes associated with invasion; for example in house sparrows increased variation in genome-wide DNA methylation was detected in invasive populations in Kenya (Liebl et al, 2013), and in invasive ascidians and corals, methylation changes quickly occurred in response to environmental challenges (Putnam et al, 2016;Huang et al, 2017). Epigenetic mechanisms are particularly relevant for the success of biological invasions as they can produce new variation (and therefore adaptation) even in the lack of genetic diversity (Hawes et al, 2018), and even more so when combined with plasticity in other regulators of genetic activity, such as non-coding RNAs or transposable elements (Stapley et al, 2015;Marin et al, 2019). Epigenetic mechanisms have also been a topic of substantial interest in social insects, where they have been demonstrated to be relevant to caste plasticity, worker division of labor, and learning and memory in social insects (Glastad et al, 2019).…”
Section: Genome Structure and Functionmentioning
confidence: 99%
“…Epigenetic mechanisms have also been suggested to be relevant in facilitating phenotypic changes associated with invasion; for example in house sparrows increased variation in genome-wide DNA methylation was detected in invasive populations in Kenya (Liebl et al, 2013), and in invasive ascidians and corals, methylation changes quickly occurred in response to environmental challenges (Putnam et al, 2016;Huang et al, 2017). Epigenetic mechanisms are particularly relevant for the success of biological invasions as they can produce new variation (and therefore adaptation) even in the lack of genetic diversity (Hawes et al, 2018), and even more so when combined with plasticity in other regulators of genetic activity, such as non-coding RNAs or transposable elements (Stapley et al, 2015;Marin et al, 2019). Epigenetic mechanisms have also been a topic of substantial interest in social insects, where they have been demonstrated to be relevant to caste plasticity, worker division of labor, and learning and memory in social insects (Glastad et al, 2019).…”
Section: Genome Structure and Functionmentioning
confidence: 99%
“…This definition broadly encompasses several levels of chromatin modifications, including DNA methylation, histone modifications and variants, and non-coding RNAs (Duncan et al 2014, Allis andJenuwein 2016). It has recently been suggested that epigenetics is a potential source of flexibility involved in the success of invasive species, allowing organisms to express advantageous phenotypes across a broader range of environments (Richards 2006, Richards et al 2017, for a recent review see Marin et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The rapid spread of invasive species in a huge spectrum of environments relies on multiple factors, from genetics to phenotypic plasticity, probably including fine molecular mechanism such as hormonal production or epigenetic gene regulation (Beldade et al , 2011; Marin et al , 2019; Stapley et al , 2015). Phenotypic plasticity, i.e., the ability of a genotype to express different phenotypes in different environments (Ghalambor et al , 2015) has been proposed as one of the most promising explanations for invasive success, particularly in the case of founder population depleted of genetic variation (Estoup et al , 2016; Marin et al , 2019). Among deleterious environments that can be encountered by invasive species, oxidative stress caused by phytosanitary products is one of them.…”
Section: Introductionmentioning
confidence: 99%